ŚRODKOWODALMATYŃSKIE KONTAKTY JĘZYKOWE W PSICH PRZYPOWIASTKACH MILJENKA SMOJE. ZAPOŻYCZENIA LEKSYKALNE W GWARZE MIEJSKIEJ SPLITU - GIEL, KARINA (Slavia Occidentalis, 2020)
This article has been written following a thesis in which I analyse borrowings from foreign languages in the urban dialect of Split, with references to Pasje novelete by Miljenko Smoje. To this end, I have conducted a lexical and etymological survey on the vocabulary excerpted from the book and I have delved into linguistic statistics. Consequently, I have documented the number and frequency of words borrowed from foreign languages. I also present a detailed calculation of the relationships between the borrowings and juxtaposed with the native vocabulary. In addition, I present a historical outline of the contacts between Croatian and other languages. I describe their intensity and the recent situation as reflected in the lexical area of the Croatian language. Finally, I make several comments on the semantic characteristics of loan words.